Is it feasible for European laboratories to use SI units in reporting results? - Zaninotto, Martina; Agnello, Luisa; Dukic, Lora; Šálek, Tomáš; Linko-Parvinen, Anna; Kalaria, Tejas; Vermeersch, Pieter; European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) Committee-Harmonization (C-H) and Committee-Postanalytical Phase (C-POST) (Clinical chemistry and laboratory medicine, 2025)
The ultimate goal of harmonization, crucial to quality in laboratory medicine, is to improve patient outcomes by providing accurate, actionable laboratory information. Patients and healthcare professionals assume that clinical laboratory tests performed by different laboratories at different times on the same type of sample are comparable, and that results can be reliably and consistently interpreted. In this context the reporting units for tests can have a considerable influence on the numeric result. The harmonization of measurement units in laboratory report, leads to the provision of interchangeable and comparable results, thus maximizing the validity of laboratory information, and assuring a more accurate diagnosis and better treatment for the patient. However, although considerable efforts have been made in recent years, the criticisms continue. This opinion paper, prepared jointly by EFLM Committee Harmonization (C-H) and Committee Postanalytical phase (C-POST), describes the "general pragmatic approach" proposed in the drafting of guidelines for the harmonization of measurement units in reporting results, in order to ensure they are used as widely as possible.
Keywords: laboratoře; reporting results; klinické laboratoře; Clinical Laboratory Techniques; international system of units (SI); Laboratories, Clinical; klinické laboratorní techniky; Humans; Laboratories; lidé; measurement units; Europe; Evropa; harmonization